An Evolutionary Game Model on Public Participation in Public-Private Partnerships - Danrong Song; Yan Sun; Yu Fan (Advances in Civil Engineering)
Effective participation of the general public in public-private partnerships (PPPs) can coordinate the multidemands of stakeholders and improve the scientificity of decision-making on infrastructure and public utility projects. However, excessive public participation may aggravate the complexity of PPPs and delay the progress of developing PPP projects. Accordingly, the appropriate participation of the general public is essential in the implementation of PPPs. This study examines the boundary conditions and the effective thresholds of public participation in adjusting the cooperative behaviors of both the government and the private investor in PPPs through an analysis of the evolution paths and dynamic balances of the strategy choices between the two parties. The results indicate that public participation in PPPs has the particularity of adjusting the partnership between the two parties. The results also suggest that public participation is not always effective and there are differences in the degree of public participation in the various strategy behaviors in which the government and the private investor choose to cooperate.